2022
DOI: 10.1021/acs.est.2c00981
|View full text |Cite
|
Sign up to set email alerts
|

Subsurface Manure Injection Reduces Surface Transport of Antibiotic Resistance Genes but May Create Antibiotic Resistance Hotspots in Soils

Abstract: Compared to surface application, manure subsurface injection reduces surface runoff of nutrients, antibiotic resistant microorganisms, and emerging contaminants. Less is known regarding the impact of both manure application methods on surface transport of antibiotic resistance genes (ARGs) in manure-amended fields. We applied liquid dairy manure to field plots by surface application and subsurface injection and simulated rainfall on the first or seventh day following application. The ARG richness, relative abu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…Endophytic fungi live in plants, and this special environment makes it easier for these fungi to play a role in biocontrol compared to other saprophytes and epiphytes. Zhang L. et al (2022) isolated 144 endophytes from different tissues of medicinal plants, among which strain 8ZJF-21 showed broad-spectrum antifungal activity and promoted plant growth by producing a variety of extracellular enzymes and metabolites. Wood saprophytes are regarded as forest cleaners.…”
Section: Prediction and Analysis Of The Functional Genes Of Metabolic...mentioning
confidence: 99%
See 1 more Smart Citation
“…Endophytic fungi live in plants, and this special environment makes it easier for these fungi to play a role in biocontrol compared to other saprophytes and epiphytes. Zhang L. et al (2022) isolated 144 endophytes from different tissues of medicinal plants, among which strain 8ZJF-21 showed broad-spectrum antifungal activity and promoted plant growth by producing a variety of extracellular enzymes and metabolites. Wood saprophytes are regarded as forest cleaners.…”
Section: Prediction and Analysis Of The Functional Genes Of Metabolic...mentioning
confidence: 99%
“…In addition, applying cow manure for many years easily causes heavy metal accumulation in soil. If not treated properly before application, the remaining harmful bacteria would disrupt the ecological balance of soil microorganisms and threaten soil security ( Hilaire et al, 2022 ). Furthermore, the residual antibiotics (such as tetracycline and sulfanilamide antibiotics) in cow manure can remain in soil for several years, leading to the evolution of antibiotic resistance genes in pathogenic bacteria, thereby increasing the abundance of antibiotic resistance genes in soil and damaging soil health ( Du et al, 2022 ; Fuchs et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Manure application, both as deliberate fertilizer treatments and the natural deposition during grazing, likely influences ARGs prevalence in soils, which provides spatially and temporally variable inputs ( Hilaire et al, 2022 ). Studies have shown that this can amplify ARGs levels in the soils and downstream environments ( Heuer et al, 2011 ; Jadeja and Worrich, 2022 ; Zhang et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Antibiotics in animals can select antibiotic-resistant bacteria in the GIT microbiome, which enhances the transfer of ARGs in their manure ( Landers et al, 2012 ; Shterzer and Mizrahi, 2015 ). Further, antibiotics themselves are not always fully absorbed in the body and thus may be discharged unchanged in the waste, resulting in high antibiotic residuals in the downstream environment ( Hilaire et al, 2022 ). Introduction of animal manure may represent a critical pathway for resistance element introduction into the soil ( Yang et al, 2019a , b ) ( Supplementary Figure S1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Increasing studies have shown that ecological niches rich in nutrients and bacterial communities, such as wastewater treatment plants, rivers, oceans, and soils, , are ideal settings for the occurrence, evolution, and spread of antibiotic resistance genes (ARGs) . Soil, the most biodiverse habitat containing the most diverse microorganisms in the planetary health system, , has become one of the major reservoirs of environmental ARGs with high diversity and abundance. , This was mainly ascribed to intensive agricultural practices, including reclaimed water irrigation and applications of manure, sewage sludge, and composts. Furthermore, pollutants (e.g., pesticides, antibiotics, and heavy metals) may also facilitate the evolution and dissemination of ARGs between soil microbiota via selecting the existing genes, , stimulating genetic mutation, and/or promoting horizontal gene transfer (HGT). , ARGs enriched in soils can potentially disseminate AMR from soil microbiota to plant microbiota, thus spreading to humans via food chains. , This would further aggravate AMR threats to human health and ecological security . Hence, it is of increasing significance to alleviate ARG burdens in soil ecosystems and their influences on global health.…”
Section: Introductionmentioning
confidence: 99%